Structural Response of Submerged Air-Backed Plates by Experimental and Numerical Analyses - Lloyd Hammond; Raphael Grzebieta (Shock and Vibration)
This paper presents the results of a series of small-scale underwater shock experiments that measured the structural responses of submerged, fully clamped, air-backed, steel plates to a range of high explosive charge sizes. The experimental results were subsequently used to validate a series of simulations using the coupled LS-DYNA/USA finite element/boundary element codes. The modelling exercise was complicated by a significant amount of local cavitation occurring in the fluid adjacent to the plate and difficulties in modelling the boundary conditions of the test plates. The finite element model results satisfactorily predicted the displacement-time history of the plate over a range of shock loadings although a less satisfactory correlation was achieved for the peak velocities. It is expected that the predictive capability of the finite element model will be significantly improved once hydrostatic initialisation can be fully utilised with the LS-DYNA/USA software.